2016
DOI: 10.1007/s12671-015-0485-5
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in Parenting and Coparenting

Abstract: Mindfulness has been established as a critical psychosocial variable for the well-being of individuals; however, less is understood regarding the role of mindfulness within the family context of parents, coparents, and children. This study tested a model examining the process by which parent dispositional mindfulness relates to parenting and coparenting relationship quality through mindful parenting and coparenting. Participants were 485 parents (59.2% mothers) from three community samples of families with you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 54 publications
4
48
0
Order By: Relevance
“…As a secondary step, the corresponding authors of the studies identified from the database searches were emailed, seeking additional contributions (including unpublished data), consistent with the study's eligibility criteria. We received responses from nine authors (within the 1‐month response window specified), resulting in an additional three studies that met our eligibility criteria (Parent, McKee, Rough, & Forehand, ; Parent, McKee, Anton, et al ., ; Schonert‐Reichl et al ., ). Lastly, the reference lists of the articles identified from the literature search were inspected for any additional relevant articles.…”
Section: Methodsmentioning
confidence: 99%
“…As a secondary step, the corresponding authors of the studies identified from the database searches were emailed, seeking additional contributions (including unpublished data), consistent with the study's eligibility criteria. We received responses from nine authors (within the 1‐month response window specified), resulting in an additional three studies that met our eligibility criteria (Parent, McKee, Rough, & Forehand, ; Parent, McKee, Anton, et al ., ; Schonert‐Reichl et al ., ). Lastly, the reference lists of the articles identified from the literature search were inspected for any additional relevant articles.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade, several researchers, particularly those interested in family and parent–child relationships, have been showing an increasing interest in the study of the applications of mindfulness to the parenting context (e.g., Dumas, 2005; Singh et al, 2007; Bögels and Restifo, 2014; Parent et al, 2016a). Mindful parenting is a parental approach that can be simply described as bringing non-judgmental, compassionate, and present-centered awareness into parent–child interactions (Kabat-Zinn and Kabat-Zinn, 1997; Bögels and Restifo, 2014; Bögels et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When parents integrate mindfulness into the parenting process, they may have more awareness about their parenting practices. Correlational studies do find a significant association between mindful parenting and traditional parenting practices ( Geurtzen et al, 2015 ; Parent et al, 2016a ). Furthermore, the indirect effect of mindful parenting on children’s outcome through traditional parenting practices has been found across different developmental stages ( Parent et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mother–child dyads were used in the current study. Previous research that investigated the relationship between mindful parenting and parenting practice has mainly focused on parent-reported data (e.g., Geurtzen et al, 2015 ; Parent et al, 2016a ), which may increase the risk of common method bias. In the current study, parenting practice was reported by the child, which was specified as children’s perceived maternal warmth, as well as children’s own dispositional mindfulness.…”
Section: Introductionmentioning
confidence: 99%